Implementasi Karakter Kepemimpinan Musa Kedalam Bingkai Pelayanan Hamba Tuhan - Restu Gulo (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
At present, sometimes in today’s ministry activities, God’s servants experience degradation of faith and character, triggered because they are not strong enough to deal with complex challengs and problems and end up leaving the ministry. This article aims to answer existing problems by discussing a character named Moses. Through his leadership character he becomes an inspirational figure that can be implemented by God’s servants into the framework of his ministry. As for the results of the character of Moses that needs to be possessed is, a gentle heart, loyal to God, humble and relies on God in ministry. This article was written using a qualitative method of library approach. The final conclusion of the writer is that the character of Moses leadership within the framework of serving God’s servant greatly contributes to answering the problems that occur among God’s servants today.